A New Record of Piper Minutistigmum C. DC. (Piperaceae) for the Flora in Vietnam - Chinh, Hoang Van; Hoi, Tran Minh; Dai, Do Ngoc (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2DO - 10.25073/2588-1140/vnunst.4850, 2019)
Abstract: Genus Piper has about 1,500 species mainly distributed in the tropical, 43 of which are recorded in Vietnam. This paper reports on the newly recorded Piper minutistigmum C. DC. for the flora of Vietnam. The voucher specimens, collected in Thanh Hoa province (Ben En National Park), Nghe An province (Pu Mat National Park: Khe Kem), Ha Tinh province (Vu Quang National Park: Doc De), are deposited in the Herbarium of the Faculty of Biology, Vinh University and the Herbarium of the Institute of Ecology and Biological Resources in Hanoi, Vietnam. Keywords: Piper minutistigmum , Piperaceae, National Park. References: [1] A. Chaveerach, R. Sudmoon T. Tanee, P. Mokkamul, Three new species of Piperaceae from Thailand, Acta Phytotaxonomica Sinica 44 (2006) 447-453. [2] Y. Cheng, N. Xia, M.G. Gilbert, Piperaceae, in Flora of China Vol. 4. Edited by Z. Wu & P.H. Raven, Missouri Botanical Garden, St.Louis, Missouri, 1999, pp. 110-129. [3] Lê Thị Hương, Lê Đông Hiếu, Trần Minh Hợi, Đỗ Ngọc Đài, Piperboehmeriaefolium (Piperaceae) loài bổ sung cho hệ thực vật Việt Nam, Báo cáo Khoa học về Nghiên cứu và Giảng dạy Sinh học ở Việt Nam, Hội nghị Khoa học Quốc gia lần thứ 3, NXB Nông nghiệp Hà Nội, Quy Nhơn, 2018, trang 529-531. [4] Nguyễn Kim Đào, Họ Piperaceae trong Nguyễn Tiến Bân (Chủ biên), Danh lục các loài thực vật Việt Nam, tập 2, NXB. Nông nghiệp, Hà Nội, 2003, trang 115-122. [5] Lê Đông Hiếu, Đỗ Ngọc Đài, Trần Minh Hợi, Đa dạng họ Hồ tiêu (Piperaceae) ở Bắc Trung Bộ, Tạp chí Nông nghiệp và Phát triển Nông thôn 4 (2017) 92-97. [6] Phạm Hoàng Hộ, Piperaceae - Họ Hồ tiêu, Cây cỏ Việt Nam, Quyển I. NXB Trẻ, Tp Hồ Chí Minh, 1999, trang 228-301. [7] A. Chaveerach, P.Mokkamul, R. Sudmoon, T. Tanee, Ethnobotany of the genus Piper (Piperaceae) in Thailand, Ethnobotany Research & Applications 4 (2006) 223-231.